PENGARUH CURRENT RATIO, TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PT. INTAN WIJAYA INTERNASIONAL,TBK - Ade Ulfa Utami; Hariyanti Hariyanti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The purpose of this study was to determine the effect of the current rasio of total asset turnover to return on asset at PT. Intan Wijaya Internasional, Tbk in 2014-2018. The types and the sources of data that the writer used are qualitative data and quantitative data. The results showed that partially the current ratio had a positive effect but did not significant effect on return on assets. Simultaneously, the variable current ratio, total asset turnover has a positive but not significant effect on retunt on assets. The calculation of the multiple correlation coefficient is 24,3% which means the current ratio and total asset turnover has a positive but low effect ob return on assets. The calculation of the coefficient of determination is 5,9% by return on assets can be explained by the current ratio, total asset turnover.